The Concept of Repentance Imam Al-Ghazali's Perspective - Bagas Dhiyaulhaq (Yayasan Bayt Shufiya Nusantara, 2023)
This article aims to explain the concept of repentance according to Imam al-Ghazali. The method used is library research with a descriptive-analytical approach to al-Ghazali's works, especially in the field of Sufism and Islamic ethics. The results of the study show that according to al-Ghazali, repentance is a spiritual process consisting of three main elements: knowledge of sin, deep repentance, and a strong determination not to repeat mistakes. True repentance must be accompanied by a change of behavior and a sincerity of heart in returning to the way of God. For al-Ghazali, repentance not only serves as a cleanser for sins, but also as a means of purifying the soul and forming a pious personality. This concept reflects the depth of Islamic spirituality that emphasizes the importance of self-awareness and sustainable moral development.